2009
DOI: 10.1007/bf03179220
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of the pectin lyase and protease produced byPenicillium velutinum grown onEichhornia crassipes under solid state fermentation

Abstract: Penicillium velutinum van Beyma grown on water hyacinth Eichhornia crassipes (Mart.) Solms. wastes as a rich organic source under conditions of solid state fermentation was selected in a preliminary screening for producing interesting levels of pectin lyase (PL) and protease. Addition of some natural additives to the fermentation medium improved the potentiality of enzymes production. PL and protease secreted by P. velutinum under these conditions were purified to electrophoretic homogeneity using ammonium sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
1
5
2
Order By: Relevance
“… 32 . In any case, we found that ammonium sulfate maximized protease production, in contrast to previous studies indicating that peptone or yeast extract was more advantageous 19 , 30 , 37 , 38 .…”
Section: Resultscontrasting
confidence: 99%
“… 32 . In any case, we found that ammonium sulfate maximized protease production, in contrast to previous studies indicating that peptone or yeast extract was more advantageous 19 , 30 , 37 , 38 .…”
Section: Resultscontrasting
confidence: 99%
“…However, a dissimilar trend of lipase and protease production was also reported when the same strain of Penicillium simplicissimum was grown in castor bean waste under SSF conditions, which is in contrast to our findings [31]. The opposite profile of lipase and protease production by Pseudomonas aeruginosa was also reported by Mahanta et al [32] in SSF using Jatropha seed cake as substrate, indicating that the maximum protease and lipase production was observed on the 3rd and 5th day of fermentation, respectively. This suggests that kinetic parameters of enzyme production may vary according to culture conditions, particularly strain and substrate used.…”
Section: The Kinetics Of Enzyme Production and Cell Growthcontrasting
confidence: 84%
“…Adding additional olive oil in the culture media did not increase the lipase production (data not shown). The maximum production of lipase and protease from C. utilis in SSF using unsupplemented olive cake was 14.31 and 58 Ug -1 of substrate, respectively, comparable or higher that the lipase or protease activity obtained with other microorganisms and solid substrates [12,13,30,32]. Nevertheless, lipolytic activity seems to be much lower than this produced by C. rugosa in SSF by using coconut oil cake as a Fig.…”
Section: The Kinetics Of Enzyme Production and Cell Growthmentioning
confidence: 58%
“…All four species are well known for their wide metabolic abilities and are constantly reported as being useful in industry and biotechnology. Some notable examples are: the fermentation of katsuobushi into karebushi (traditional Japanese cuisine) by A. pseudoglaucus [ 74 ]; the production of volatile compounds for traditional Chinese dry sausages by A. pseudoglaucus [ 75 ]; the production of mycophenolic acid by A. pseudoglaucus [ 76 ]; bioremediation by A. sydowii [ 77 , 78 , 79 ]; the production of monoterpenoids by A. sydowii [ 80 ]; the production of different polyketides by A. sydowii and P. velutinum [ 80 , 81 , 82 ]; the production of xylanases by A. sydowii [ 83 ]; the production of fructooligosaccharides by P. expansum [ 84 ]; the production of patulin, citrinin, and lipases by P. expansum [ 85 , 86 , 87 ]; and the production of pectin lyase and protease by P. velutinum [ 88 ]. The isolation and characterization of novel environmental strains of microorganisms that are already known for their biotransformation abilities may lead to the further improvement and better understanding of biotechnological processes, especially in the case of extremophilic strains (such as those in the Arctic), which might possess cold-adapted variants (protein muteins) of already known enzymes.…”
Section: Discussionmentioning
confidence: 99%